Theory and practice of integrated pest management - Arora, Ramesh; Balwinder Singh, Ph. D.; Dhawan, A. K. (Scientific Publishers (India), 2012)
Papers presented at the 'Winter School' on Advances in Agricultural Entomology held at Punjab Agricultural University during December 2010 to January 2011.